Positive psychological capital and its influencing factors among parents of children with leukemia - Niu Minrui; Dong Shuwan; Wang Huicai; Chen Jinrong; Alipati Tailaiti; Min Min (Sichuan jingshen weisheng, 2023)
BackgroundPsychological capital has a significant impact on individual post-traumatic growth and well-being. However， there is limited research on the psychological capital and its related factors among parents of children with leukemia.ObjectiveTo explore the psychological capital status of parents of children with leukemia and analyze its influencing factors， in order to provide references for formulating intervention strategies to improve the psychological capital among these parents.MethodsFrom March 2021 to April 2022， 143 parents of children diagnosed with leukemia from the Department of Pediatrics at the First Affiliated Hospital of Xinjiang Medical University was selected. The general demographic information questionnaire， Positive Psychological Capital Questionnaire （PPQ）， Chinese-Posttraumatic Growth Inventory （C-PTGI） and Index of Well-being Scale （IWB） were used to investigate the participants. Multiple linear regression analysis was used to analyze the influencing factors of psychological capital.ResultsThe PPQ total score for parents of children with leukemia was （113.48±15.80）. The PPQ total score showed positive correlations with the scores of C-PTGI and IWB （r=0.727， 0.598， P<0.01）. The course of children's illness （β=0.136， P=0.017）， parental education level （β=0.139， P=0.012） and C-PTGI score （β=0.622， P<0.01） were influencing factors of psychological capital among these parents， collectively explaining 57.6% of the total variability.ConclusionThe level of positive psychological capital among parents of children with leukemia warrants improvement. Factors including course of the children's illness， parental education level and post-traumatic growth significantly impacted their psychological capital.［Funded by Innovation and Entrepreneurship Project for Graduate Students of Xinjiang Medical University （number， CXCY2022047）］